Pedagogical Characteristics of Nurturing Patriotism in Students’ Souls - Gaybullyoevna, Habibova Guliya (Journal of Innovation in Education and Social Research, 2024)
This article highlights the distinctive features of the process of nurturing patriotism in students' souls within the framework of teaching pedagogical and psychological subjects. The content of the article emphasizes the unique characteristics of this process.